Identification and Biochemical Characterization of Halisulfate 3 and Suvanine as Novel Inhibitors of Hepatitis C Virus NS3 Helicase from a Marine Sponge - Atsushi Furuta; Kazi Abdus Salam; Idam Hermawan; Nobuyoshi Akimitsu; Junichi Tanaka; Hidenori Tani; Atsuya Yamashita; Kohji Moriishi; Masamichi Nakakoshi; Masayoshi Tsubuki; Poh Wee Peng; Youichi Suzuki; et al. (Marine Drugs, 2014)
Hepatitis C virus (HCV) is an important etiological agent that is responsible for the development of chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma. HCV nonstructural protein 3 (NS3) helicase is a possible target for novel drug development due to its essential role in viral replication. In this study, we identified halisulfate 3 (hal3) and suvanine as novel NS3 helicase inhibitors, with IC50 values of 4 and 3 µM, respectively, from a marine sponge by screening extracts of marine organisms. Both hal3 and suvanine inhibited the ATPase, RNA binding, and serine protease activities of NS3 helicase with IC50 values of 8, 8, and 14 µM, and 7, 3, and 34 µM, respectively. However, the dengue virus (DENV) NS3 helicase, which shares a catalytic core (consisting mainly of ATPase and RNA binding sites) with HCV NS3 helicase, was not inhibited by hal3 and suvanine, even at concentrations of 100 µM. Therefore, we conclude that hal3 and suvanine specifically inhibit HCV NS3 helicase via an interaction with an allosteric site in NS3 rather than binding to the catalytic core. This led to the inhibition of all NS3 activities, presumably by inducing conformational changes.